2019
DOI: 10.1098/rspb.2019.0924
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod–bacteria interactions influence assembly of aquatic host microbiome and pathogen defense

Abstract: The host-associated microbiome is vital to host immunity and pathogen defense. In aquatic ecosystems, organisms may interact with environmental bacteria to influence the pool of potential symbionts, but the effects of these interactions on host microbiome assembly and pathogen resistance are unresolved. We used replicated bromeliad microecosystems to test for indirect effects of arthropod–bacteria interactions on host microbiome assembly and pathogen burden, using tadpoles and the fungal amphibian pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 71 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…An ever-increasing body of literature has demonstrated the importance of diverse microorganisms in ecology, such as biogeochemical cycling ( Rousk and Bengtson, 2014 ), ecosystem health ( Hooper et al, 2005 ), and disease prevention in hosts ( Hamdi et al, 2011 ; Greenspan et al, 2019 ). In our study, we documented a drastic decrease in the diversity of the wild-caught horseshoe crabs microbiome and significant shifts in microbial community structure shortly after entering captivity.…”
Section: Discussionmentioning
confidence: 99%
“…An ever-increasing body of literature has demonstrated the importance of diverse microorganisms in ecology, such as biogeochemical cycling ( Rousk and Bengtson, 2014 ), ecosystem health ( Hooper et al, 2005 ), and disease prevention in hosts ( Hamdi et al, 2011 ; Greenspan et al, 2019 ). In our study, we documented a drastic decrease in the diversity of the wild-caught horseshoe crabs microbiome and significant shifts in microbial community structure shortly after entering captivity.…”
Section: Discussionmentioning
confidence: 99%
“…their skin microbiomes provide a model for understanding the processes shaping the forces of colonization, competition and coexistence of microbial species on a vertebrate host, and quantifying the emergent functional properties of these microbial communities and their consequences for the host. The properties of this system make it well suited to testing the applicability of established ecological theory derived from eukaryotic communities to prokaryotic assemblages associated with animals, plants and soils, including the relationship between biodiversity and ecosystem function (e.g., see Koskella et al, 2017;Greenspan et al, 2019).…”
Section: Environmental Microbial Diversity Influence Temporal Microbimentioning
confidence: 99%
“…Anti-fungal metabolite production by bacteria increases dramatically when the bacteria are co-cultured (Loudon et al, 2014a), suggesting that microbiome-mediated host protection is likely a function of synergistic interactions among community members. Greater microbiome diversity may therefore offer increased protection from pathogens (e.g., Piovia-Scott et al, 2017;Antwis and Harrison, 2018;Greenspan et al, 2019; but see Becker et al, 2019), but the ecological processes structuring and maintaining microbial diversity on amphibian skin remain relatively understudied, especially at the level of the individual (Loudon et al, 2014b(Loudon et al, , 2016Longo and Zamudio, 2017;Hughey et al, 2019). For example, the diversitystability hypothesis predicts that more diverse communities should be more resistant to disturbance, and several empirical studies support this hypothesis in plant community assemblages (McCann, 2000;Costello et al, 2012), but it is unclear whether this theory is also relevant at the scale of host-associated microbial communities (Costello et al, 2012, but see Koskella et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both environmental and host-specific factors are predictors of amphibian skin microbiome structure 18 , 19 . Among the environmental factors influencing the cutaneous bacterial communities of amphibians, life stage transitions 18 , 20 , 21 , diet composition 22 , disease 23 , elevation 24 , microbial interactions 25 , 26 , season 17 , 27 , temperature 14 , water pH 28 , contaminants 28 , captivity 29 , 30 , habitat fragmentation 31 , 32 , trophic network interactions 33 , host assemblages 34 , and precipitation have been identified 35 . Host associated factors are less studied but clearly also play a role because multiple studies have demonstrated that the skin microbiomes of co-occurring species are significantly different 18 , 29 , 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%